Cultural Levels and Pre-Service Teachers' Behaviour Towards the Use of Open Educational Resources. Issue 1 (13th December 2021) - Asghar, Muhammad Zaheer; Erdoğmuş, Yasemin Kahyaoğlu; Seitamaa-Hakkarainen, Pirita
The behaviour to use innovation and technology for teaching, learning, and research is influenced by different levels of culture, ranging from the supranational, professional, and organizational to the individual level. The current study focused on the organizational, professional, and individual levels of cultural influence on pre-service teachers' intentions towards the use of open educational resources (OERs). This study is based on the theory of planned behaviour (TPB) and different levels of culture for innovation and technology usage. A survey was conducted on pre-service teachers (n = 376) enrolled in the universities of Punjab (Pakistan). Structural equation modeling (SEM) was applied through smart-PLS. The results revealed that pre-service teachers were aware of the importance of OERs. It was found that pre-service teachers' intentions played an important role towards their actual behaviour to use OERs. Personal level culture and perceived behavioural control influences the pre-service teacher's intentions to use open educational resources. The study has policy and practice implications for developing a social, cultural, and psychological environment to enhance pre-service teachers' intentions to use OERs. Future studies may be conducted on the effect of supranational and national culture on institutional policies designed to adopt OERs.